Clinical Anatomy of Mesenteric Hemangiosarcoma in Labrador dog - K. T., Lakshmishree; M., Dhoolappa; S., Malatesh D.; S., Manjunatha S.; Chavan, Yuvaraj; Honnatti, Umesh (Indian Journal of Veterinary Anatomy, 2023)
The of locations and visualization of the abdominal organs are essential for veterinary practice. A thirteen year old female Labrador dog was presented to the Veterinary Clinical Complex, Veterinary College, Shivamogga with history of inappatance. The dog was lethargic and a mass palpable in the abdominal region. Ultrasonographic examination of abdomen revealed calcified mass in left abdominal region. As the prognosis was graved, with the consent of owner, the dog was euthanized and embalmed in Department of Veterinary Anatomy, Veterinary College Shivamogga under willed-body program. On dissection, a mass of about 325gms attached with the mesentery was found in the abdominal cavity. Tissue samples were taken for histology and routine H&E and toluidine blue staining was performed to observe metastatic lesions. Based on clinical, ultrasonography and histological observations the present case was diagnosed as mesenteric hemangiosarcoma.